Pengenalan Pajak pada Siswa SMA Muhammadiyah 4 Lamongan - Qosim Qosim; Rita Nataliawati; Dwi Pertiwi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
Taxes have a very important role in the life of the country because taxes are needed in financing most of the country's development interests so that people's welfare is achieved. Public awareness is needed in order to create a tax orderly culture for the people of Indonesia. One of the efforts to raise public awareness can be done through outreach to school students so that early awareness of taxes has been formed. Institut Teknologi dan Bisnis Ahmad Dahlan community service team carried out socialization to Senior High School of Muhammadiyah 4 Lamongan students regarding taxes using the offline method. The students responded enthusiastically to the tax introduction activity. With this activity, the community service team hopes that Indonesian people will become more aware of tax obligations.